Dekonstruksi Diatetif dalam Upaya Diferensiasi Judul pada Naskah Artikel Ilmiah: Studi Analisis Proposisi: Tinjauan Psikolinguistik - Nicky Rosadi (LITERATUS, 2021)
This study attempts to describe the descriptive deconstruction of the title of a scientific article whose text is derived from the conversion of research reports. The method used in this study is a qualitative method using a propositional analysis model. Proposition analysis is an analytical model that seeks to dissect the structure of the language based on the structure outside the language. Therefore, this field of study is included in the field of psycholinguistic studies because it raises language problems based on human psychological elements. In this study, it is known that research reports and scientific articles have different reader objectives. Each has a different motive of interest. Research reports have expository motifs with specific audiences, such as leaders or related stakeholders. For this reason, the description and presentation are detailed and detailed. While scientific articles emphasize the informative side with the general target audience; academics, experts, and society in general. Because of this difference, the use of titles needs to be distinguished even though they have the same essence. This is because, by selecting the appropriate title, it is expected to increase the visitation and readability of the scientific article. One of the efforts that can be done is to diathesis deconstruct the research title. This diathesis deconstruction is based on a propositional analysis that looks at the structure of the proposition, the meaning of the predicator, and the role of the argument in the research title, which is then deconstructed by considering the construction of the previous diathesis.